Pengaruh Ukuran Perusahaan, Likuiditas, Dan Struktur Modal Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi - Silvya Reza Novita Sari; Syaiful Bahri; Nurdiana Fitriani (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This study examines the effect of firm size, liquidity, and capital structure on firm value, by including dividend policy as a moderator variable. This study focuses on food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024, given the sector's significant impact on the national economy and the varied dynamics of firm value. A quantitative approach is used using secondary data obtained from annual financial reports. Firm size is measured by the natural logarithm of total assets, liquidity by current ratio, capital structure by debt-to-equity ratio, dividend policy by dividend payout ratio, and firm value by price-to-book value ratio. The analysis uses multiple linear regression and moderated regression analysis (MRA) using SPSS. The findings show that firm size has a significant positive effect on firm value, while liquidity and capital structure have no significant effect. In addition, dividend policy does not affect the correlation between firm size, liquidity, or capital structure with firm value, suggesting that investors may prioritize other fundamental factors beyond dividend distribution. These results support signaling theory and have a real impact on the way managers and investors make decisions regarding corporate finance.